Cambridge Preparation for the TOEFL Test - Gear J. Jolene (Cambridge, Cambridge University Press, 2010)
The fourth edition of Cambridge Preparation for the TOEFL® Test provides fully updated practice in all of the language skills tested on the new TOEFL iBT, or Internet-Based Test. Included in this test preparation package is a CD-ROM that can be used to simulate the online TOEFL test or to provide feedback as a study tool. Key features of the 4th edition include: An iBT-format diagnostic test, three complete practice tests, and mini-tests in the book . Seven complete practice tests on CD-ROM. Over 200 skill-building exercises in reading, listening, speaking, and writing. Integrated-skills tasks that combine reading and listening with speaking or writing. Test-taking strategies for each skill. A special section to strengthen vocabulary, pronunciation, and grammar as well as note-taking, paraphrasing, and summarizing skills. An answer key with explanations, plus sample answers for TOEFL iBT essays and speaking responses. A complete audio program with listening exercises and practice tests.